A Qualitative Review on Halal Food: NVivo Approach - Nadia Nurul Izza; Aam Slamet Rusydiana (Universitas Darussalam Gontor, 2023)
The State of the Global Islamic Economy Report 2019/2020 notes that global Muslim spending on food is estimated to reach 1.37 trillion in 2018, growing by 5.1% from 2017. Expenditure is expected to grow by 6.3% annually to reach 2.0 trillion by 2024. Today, the Muslim consumer market has been recognized as another important segment for cross-sectoral businesses. The increasing interest has made researchers focus on the halal food sector. This study aims to identify and map research related to the development of halal food research through reputable journals indexed by Scopus with a qualitative approach using NVivo 12 Plus software. The data analyzed consisted of 372 journals published in the last 21 years (2001-2021). This study also found that halal food chain management, formal halal certification and technology that can verify and support this certification will ensure compliance with Islamic law, generate trust among consumers, and become the main strategy for accelerating sharia economic growth.